Analysis of the Influence of Motivation Factors on Employee Performance at KMU Gresik Clinic - pitra aries wibowo (Media Gizi Kesmas, 2022)
Background: The level of challenge of an organization with increasing time becomes large, but if later it will not be even greater, then it is certain that it will not follow and will be eaten by time itself or die. As a health facility that focuses mainly on eye and cataract surgery, the Utama Eye Clinic must be able to demonstrate the existence of its organization in responding to these bigger challenges. Now the biggest challenge is the quality of human resources working to reduce the rate of blindness due to cataracts which is increasing every day.Objectives: Analyzing the effect of the relationship between employee motivation on their performance at work at KMU Gresik.Methods: This research is a descriptive analytic study which was conducted using a quantitative cross sectional approach. The statistical test used was the Chi Square test. The number of respondents for filling out the questionnaire was 35 respondents. When the research was conducted in January 2018.Results: The statistical test of this study shows that there is a significant relationship between motivation and employee performance working at KMU Gresik with a correlation value of 15.251 and p-value = 0.000.Conclusions: The influence relationship between employee performance variables and employee motivation variables working at KMU Gresik is very significant, so it is recommended for employee motivation at KMU Gresik to be recognized and improved so that employee performance results increase.